The Effect of Racket String Tension at 28 lbs and 24 lbs on Smash Speed of Badminton Athletes - Rayhan Achdhika Subarjat; Komarudin; Angga M Syahid (Universitas Negeri Semarang, 2025)
Badminton is a racket sport that emphasizes movement technique training such as jumping, turning, fast arm movements and requires the right racket strings. One of the factors to get the speed of a badminton athlete's smash is one of them using the tightness of a 28 LBS and 24 LBS racket string. Therefore, this study aims to examine the effect of the tightness of the 28 LBS and 24 LBS racket strings on the speed of a badminton athlete's smash. The method used by the researcher is an experimental method with an Ex-Post Facto research design. The sample involved in this study consisted of 10 badminton athletes selected according to the criteria desired by the researcher. The instrument used uses kinovea software. The analysis of this data was taken by the researcher using the SPSS version 23 application. The data obtained by the researcher was in the form of an average value of 1.50, with a standard deviation of 0.513. The results of the homogeneity test showed that the significance value of 0.663> 0.05, so it can be concluded that the data variance is homogeneous. Along with the t-test results show that the significance value (2-tailed) is 0.000 <0.05, which means that there is a significant difference in average speed between the tightness of the 28 LBS and 24 LBS racket strings. The results of this study indicate that there is a significant effect of the tightness of the 28 LBS and 24 LBS racket strings on the speed of badminton athletes smash.